ANALISIS KEBUTUHAN AWAL PENGEMBANGAN MEDIA DALAM PELAJARAN BAHASA INDONESIA UNTUK MENGINGKATKAN KEMAMPUAN MENULIS MURID DI SEKOLAH DASAR - Nurjayanti, Eli; Subrata, Heru; Hendratno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Indonesian language is one of the lessons which must be given to the students from elementary school until university. It is because this lesson can't be separated with other knowledges. This research was to analyze media development needs as an action to improve student's writing skill in Indonesian lesson. The research method was descriptive qualitative and the research instruments were teacher's score record, interview, and questionnaire which was given to teachers and students. According to student's pre test, it could be seen the worst score was 65 and the best score was 85 with the average score 66. This problem was because teaching media was not varied, students were not interested in writing, and teaching method was not varied as well. The research result was shown most of the students need a media in comic strip to help them in writing. The research conclusion was comic strip media can be a solution to improve students' writing skill in writing a story.